2021
DOI: 10.1186/s41182-021-00297-0
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of Clonorchis sinensis infection in Guangxi, Southern China

Abstract: Background Soil-transmitted helminths (STHs), such as hookworm, roundworm and whipworm, and food-borne trematodiases, including Clonorchis sinensis, remain a public health problem worldwide, especially in tropical and subtropical regions. Objective We aimed to determine the current prevalence of these parasites in Guangxi, China, which is located in a subtropical region. Methods A cross-sectional study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…However, this correlation does not translate to a strong causation in the absence of experimental validation. Therefore, further experimental validation is necessary to clarify the impact of C. sinensis infection on HCC carcinogenesis [34][35][36]. Our data also indicated a higher prevalence of males in the C. sinensis (+) HCC group than in the C. sinensis (-) HCC group.…”
Section: Sinensis Promotes Hcc By Activating Hcc Stemnessmentioning
confidence: 61%
See 1 more Smart Citation
“…However, this correlation does not translate to a strong causation in the absence of experimental validation. Therefore, further experimental validation is necessary to clarify the impact of C. sinensis infection on HCC carcinogenesis [34][35][36]. Our data also indicated a higher prevalence of males in the C. sinensis (+) HCC group than in the C. sinensis (-) HCC group.…”
Section: Sinensis Promotes Hcc By Activating Hcc Stemnessmentioning
confidence: 61%
“…Therefore, further experimental validation is necessary to clarify the impact of C . sinensis infection on HCC carcinogenesis [ 34 36 ]. Our data also indicated a higher prevalence of males in the C .…”
Section: Discussionmentioning
confidence: 99%
“…O. viverrini is mainly restricted to Southeast Asia, O. felineus is indigenous to North Asia and Eastern Europe, and C. sinensis is prevalent in Korea, sections of Russia, China, and Vietnam ( Sripa et al ., 2021 ; Pakharukova et al ., 2023 ). According to China’s national parasite inquiry, the prevalence of Clonorchiasis has increased by about 0.37 percent since the initial examination in 1988, and a recent study found that the prevalence of C. sinensis infection is 29.3 percent ( Gao et al ., 2020 ; Jiang et al ., 2021 ). While nearly 1.2 million people reside with O. felineus in Western Siberia and other regions of the Russian Federation ( Ovchinnikov et al ., 2017 ).…”
Section: Distribution Of Liver Trematodesmentioning
confidence: 99%
“…It is estimated that around 35 million individuals are infected with this disease, with approximately 15 million of these cases being reported in China alone [ 8 10 ]. The region most severely impacted by this affliction are Guangdong Province and the Guangxi Zhuang Autonomous Region in Southern China [ 11 13 ]. C .…”
Section: Introductionmentioning
confidence: 99%